Comparison of Two Different Bonding Agents on Clinical Performance of Fissure Sealants - A. Makarem; M. Ebrahimi; M. Talebi; F. Sadeghipour (Tehran University of Medical Sciences, 2007)
Objective: Considering the fact that several bonding agents are available in market, clinical evaluations are required to find the durability of the sealants after using bonding agents. The purpose of this study was to compare the durability of the fissure sealant after applying two kinds of dentin bonding materials, AdheSE and Excite. Materials and Methods: In this clinical study sample group consisted of hundred permanent first molars teeth of forty two children. Convenience sampling method has been applied. After three, six and twelve month follow-up, marginal integrity, retention rate and caries in experimental groups were examined. Data were analyzed according to Fisher's Exact, Chi-Square and Mann-Whitney statistical tests. Results: There was no statistical significant difference between the two examined groups,considering marginal integrity, retention rate and caries. In AdheSE group, maxillary teeth had a better retention than mandibular ones. Conclusion: It seems that in pediatric dentistry use of Excite as a bonding agent before the placement of fissure sealant is preferable.